Pemanfaatan Media Mind Mapping Berbasis Project Based Learning pada Pembelajaran SKI di Madrasah Tsanawiyah Negeri 2 Bengkulu Tengah - Mukhsinul Azhar; Zurifah Nurdin (UIN Fatmawati Sukarno Bengkulu, 2024)
The purpose of this study is (1) To find out and describe the use of Mind Mapping Media based on Project Based Learning in SKI Learning at State Junior High School 2, Bengkulu Tengah. (2) To find out and describe the Implementation of Mind Mapping Media based on Project Based in State Junior High School 2, Bengkulu Tengah. (3) To find out and describe the advantages and disadvantages of Mind Mapping Media based on Project Based Learning in SKI Learning at State Junior High School 2, Bengkulu Tengah. The type of research used in this study is descriptive qualitative research, the research subjects who can provide information are the Principal or Vice Principal and Teachers. Research results (1) Utilization of Mind Mapping Media based on Project Based Learning in SKI Learning at State Junior High School 2, Central Bengkulu, Mind Mapping media based on Project Based Learning used in SKI learning is oriented towards students, so that students are able to conceptualize SKI Material and are easy to understand, are able to create interesting and active learning and are able to raise students' enthusiasm and enthusiasm in participating in learning. (2) Application of Mind Mapping Media based on Project Based Learning in SKI Learning at State Junior High School 2, Central Bengkulu, namely: a. Students are asked to form groups. b. Students pay attention to the instructions for making mind mapping given by the teacher. c. The teacher distributes a blank sheet of paper to each group. d. Students design the creation of mind mapping e. Group representatives collect the results of the mind mapping on the teacher's desk. f. Representatives of each group are appointed by the teacher to present the results of the mind mapping in front of the class. (3) The advantages and disadvantages of Mind Mapping Media based on Project Based Learning for SKI Learning at State Middle School 2, Central Bengkulu are that it can hone students' creativity, train students to think critically and the disadvantages of mind mapping media include: only being able to include important points.